1999
DOI: 10.1021/np980195c
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol Glycosides from Cassia hirsuta

Abstract: A new flavonol glycoside, kaempferol 3-O-alpha-L-rhamnopyranosyl (1-->2)-alpha-L-rhamnopyranoside (1), was isolated from the flowers of Cassia hirsuta along with two known flavonol glycosides, kaempferol 3-O-rutinoside and rutin. The structure of compound 1 has been established on the basis of spectral data and by acid hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…The FAB-MS, UV, 1 H, 13 C NMR data of compound 7 were in a good agreement with those reported for kaempferol-3-O-a-Lrhamnosyl-(1 000 -2 00 )-a-L rhamnoside (Mabry et al, 1970;Rao et al, 1998). This is the first report for the isolation and Phytochemical and biological studies of Carduus pycnocephalus L.…”
Section: Characterisation Of the Isolated Compoundssupporting
confidence: 87%
See 1 more Smart Citation
“…The FAB-MS, UV, 1 H, 13 C NMR data of compound 7 were in a good agreement with those reported for kaempferol-3-O-a-Lrhamnosyl-(1 000 -2 00 )-a-L rhamnoside (Mabry et al, 1970;Rao et al, 1998). This is the first report for the isolation and Phytochemical and biological studies of Carduus pycnocephalus L.…”
Section: Characterisation Of the Isolated Compoundssupporting
confidence: 87%
“…identification of this compound from the genus Carduus and second time in nature; it was previously isolated from Cassia hirsuta (Rao et al, 1998). Compounds 8-10 were identified by comparison of their IR, EI-MS and 1 H NMR, 13 C NMR data with the literatures as lupeol (Ahmad and Rahman, 1994), b-sitosterol and b-sitosterol-3-O-b-D-glucoside (Good and Akihisa, 1997).…”
Section: Characterisation Of the Isolated Compoundsmentioning
confidence: 96%
“…A new flavonol glycoside [kaempferol 3-O-α-L-rhamnopyranosyl (1-2)-α-L-rhamnopyranoside] has been separated from the flowers of C. hirsuta along with two known flavonol glycosides (kaempferol 3-O-rutinoside and rutin) [12]. Luximon-Ramma et al [13] report the presence of total phenolics (9-54 mg gallic acid equivalent/g dry weight), total flavonoids (3-14 mg quercetin equivalent/g dry weight) and total proanthocyanidins (2-20 mg cyanidin chloride equivalent/g dry weight) in different parts of the related species, C. fistula.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggested that 1 was a substituted labdanetype diterpene. 10 The two sugar moieties were identified as glucose (Glc) and rhamnose (Rha) on the basis of characteristic 13 11 In the 1 H NMR spectrum, anomeric protons at δ 4.42 (d, 7.6) and 5.37 (s) and a typical rhamnose methyl signal (δ 1.21, d, 6.0) were observed. The glucose had a -configuration and rhamnose had an R-configuration on the basis of the magnitude of the coupling constants of the anomeric protons, J ) 7.6 and 0 Hz, respectively.…”
Section: Resultsmentioning
confidence: 99%